Efforts to Increase the Interest and Learning Outcomes Students in Learning Indonesian Through Slipboard Media - Awliya Nur Oktadita; Cecil Hiltrimartin; Destiana Wati (Journal of Basic Education Research, 2023)
Purpose of the study: This research aims to increase class IV students' interest and learning outcomes in learning Indonesian through slip board media. Methodology: The research method used was classroom action research, which was carried out at Elementary School 07 Palembang in class IV A. The sampling technique used was purposive sampling. The data collection instruments used were observation instruments and evaluation tests. The data analysis used is qualitative descriptive techniques and quantitative percentages of student interests and learning outcomes. Main Findings: Based on the research results, it is known that there has been an increase in students' interest and learning outcomes in learning Indonesian. This means that by using slip board media, students are able to increase their learning activities. Novelty/Originality of this study: The newness of this research lies in the slip board media used by researchers, where learning Indonesian can increase students' interest and learning outcomes. The limitation of this research is that it only focuses on class IV A of elementary schools. Researchers recommend that other research develop slip board media for Indonesian language learning or use other media in order to increase the interest and learning outcomes of elementary school students.